Optogenetics-assisted characterization of parvalbumin-expressing interneurons in the dentate gyrus in freely behaving mice - Luis Fernando Cobar Zelaya (Nanyang Technological University, 2021)
In the mammalian brain, neural circuits generate all cognitive functions. Two main neuronal classes compose these circuits: Excitatory principal cells and interneurons, which balance the activity of principal neurons via inhibitory effects and control network activity in the brain. In the hippocampus, multiple types of interneurons have been classified based on their morphology, post-synaptic target or neurochemical marker. The expression of Ca2+ binding protein, parvalbumin (PV), defines a subtype of interneurons in the dentate gyrus (DG). The activity of PV+ interneurons in the DG and the control exerted over their post-synaptic targets has not been studied in vivo, due to the difficulty of recording them, owing to their low numbers and the challenge to unambiguously isolate their activity from other interneurons. In this work, I aim to characterized PV+ interneuron activity in the DG of freely behaving mice and their control over other neurons via the use of optogenetics and single-unit recording. We show that DG PV+ interneurons display a high mean firing rate, are phase-locked to theta oscillations, and lack spatial modulation in their firing during exploration. Optogenetic activation of DG PV+ interneurons resulted in a significant reduction in the firing rate of principal cells and interneurons in the DG. These results provide evidence of the inhibitory role of PV+ interneurons over other cells in the DG, and it expands our knowledge regarding the interactions between different types of neurons in the DG in vivo.